Joseph Conrad’s Lord Jim, Stein, and the use and abuse of entomology - Etienne Terblanche (Literator)
Based on an implausible perception of entomology (the study of insects), George Waddington attempts to debauch the moral integrity of the character Stein in Joseph Conrad’s much-discussed novel Lord Jim. This tarnishing is part of an overall trend to undermine the greatness of literary artworks. Waddington’s accusations against Stein and the reception of his article destabilise the novel’s and critics’ more even-minded and largely positive perception of Stein’s nature, casting doubt about the novel’s morality as a whole. The present piece reads against the grain of this trend and reconsiders the critical reading of Lord Jim in terms of a more accurate appraisal of entomology’s praxes and values, and Stein’s entomology in particular. The author is a practising lepidopterist (student of butterflies and moths), which is the platform on which the piece offers its critique.